Physiological Responses and Time-Motion Analysis of Kickboxing: Differences Between Full Contact, Light Contact, and Point Fighting Contests. Issue 9 (September 2021) - Ouergui, Ibrahim; Benyoussef, Amal; Houcine, Nizar; Abedelmalek, Salma; Franchini, Emerson; Gmada, Nebil; Bouhlel, Ezdine; Bouassida, Anissa
Abstract : Abstract: Ouergui, I, Benyoussef, A, Houcine, N, Abedelmalek, S, Franchini, E, Gmada, N, Bouhlel, E, and Bouassida, A. Physiological responses and time-motion analysis of kickboxing: differences between full contact, light contact, and point fighting contests. J Strength Cond Res 35(9): 2558–2563, 2021—This study investigated the physiological responses and time structure of kickboxing styles (full contact, light contact, and point fighting). Blood lactate [La] before and after combats, mean heart rate (HRmean), percentage of time spent in HR zones, and rating of perceived exertion were assessed. Time spent in high-intensity activities (HIAs), low-intensity activities (LIAs), and referee pauses (P) were recorded according to rounds (R) and kickboxing styles. [La] increased statistically significant after kickboxing combats ( p < 0.001) and was higher after light contact compared with point fighting ( p = 0.029). HRmean did not differ between kickboxing specialties ( p = 0.200). However, more time was spent on HR zones 4 and 5 (Z4: 80–90% and Z5: 90–100% HRmax) than in other zones (all p < 0.001). Rating of perceived exertion scores were higher after light and full contact combats compared with point fighting ( p = 0.007 and 0.093, respectively). High-intensity activities, LIAs, and pauses did not statistically differ across rounds ( p > 0.05). Moreover, HIA values were lower than LIA (all p < 0.001), and HIA and LIA were higher than pause for all rounds and styles (all p < 0.001). Full contact elicited higher HIA compared with point fighting ( p = 0.003, 0.001, and 0.002 for round 1, 2, and 3, respectively). Coaches and strength and conditioning professionals should emphasize anaerobic and muscle power development for all disciplines, especially for full and light contact and maximal aerobic power enhancement by targeting specific HR zones. Moreover, training regimen may include high-intensity interval training to mimic these sports' specificity using the effort-pause ratios according to different kickboxing sports.